2021
DOI: 10.1038/s41598-021-84954-8
|View full text |Cite
|
Sign up to set email alerts
|

Shared cognitive mechanisms of hypnotizability with executive functioning and information salience

Abstract: In recent years, evidence linked hypnotizability to the executive control and information salience networks, brain structures that play a role in cognitive conflict resolution and perseveration (insisting on applying a previously learned logical rule on a new set). Despite the growing body of neuroimaging evidence, the cognitive phenotype of hypnotizability is not well understood. We hypothesized that higher hypnotizability would correspond to lower perseveration and set-shifting. Seventy-two healthy adults we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 77 publications
(130 reference statements)
2
11
0
1
Order By: Relevance
“…Furthermore, in a large sample (𝑁 = 180), Dienes et al (2009) found no correlation between hypnotic-suggestibility and cognitive capabilities. The present study indicates why the findings of studies investigating the relation between hypnotic-suggestibility and cognitive control are inconclusive (e.g., Dienes et al, 2009;Faerman & Spiegel, 2021;Ludwig et al, 2013;Parris, 2017;Terhune et al, 2017). Studies investigating the relation between hypnotizability and other processes must take into account the bifactorial nature of the scales employed.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, in a large sample (𝑁 = 180), Dienes et al (2009) found no correlation between hypnotic-suggestibility and cognitive capabilities. The present study indicates why the findings of studies investigating the relation between hypnotic-suggestibility and cognitive control are inconclusive (e.g., Dienes et al, 2009;Faerman & Spiegel, 2021;Ludwig et al, 2013;Parris, 2017;Terhune et al, 2017). Studies investigating the relation between hypnotizability and other processes must take into account the bifactorial nature of the scales employed.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, in a large sample ( = 180), Dienes et al (2009) found no correlation between hypnotic-suggestibility and cognitive capabilities. The present study indicates why the findings of studies investigating the relation between hypnotic-suggestibility and cognitive control are inconclusive (e.g., Dienes et al, 2009;Faerman & Spiegel, 2021;Ludwig et al, 2013;Parris, 2017;Terhune et al, 2017). Studies investigating the relation between hypnotizability and other processes must take into account the bifactorial nature of the scales employed.…”
Section: Discussionmentioning
confidence: 74%
“…Executive functions. Hypnosis enhances executive functions such as those of inhibition, emotional control and mental flexibility [26][27][28]. Hypnotic suggestions engage individuals in new and adaptive patterns of thinking, feeling and behaving.…”
Section: The Role Of Clinical Hypnosis In Metacognitive Knowledgementioning
confidence: 99%
“…Faerman et al [26] provided evidence that the tendency to respond to hypnosis is linked to cognitive flexibility. The researchers selected 72 participants who firstly completed the Harvard Group Scale of Hypnotic Susceptibility and afterwards two neuropsychological tests that assess the cognitive phenomenon known as perseveration.…”
Section: The Role Of Clinical Hypnosis In Adaptabilitymentioning
confidence: 99%